1899 Annotated Statutes of the Indian Territory, at 243-44, ch. 19, pt. 53, § 1252 - (:unkn) unknown (General Publisher, 1899)
Any person who shall sell, barter or exchange, or otherwise dispose of, or in any manner furnish to any person, any dirk or bowie knife, or a sword or a spear in a cane, brass or metal knucks, or any pistol of any kind whatever, except such as are used in the army or navy of the United States, and known as the navy pistol, or any kind of cartridge for any pistol, or any person who shall keep any such arms or cartridges for sale, shall be guilty of a misdemeanor.
--
Keywords: TRANSFER